Konstitusionalitas Sistem Proporsional Terbuka Pasca Putusan Mahkamah Konstitusi Nomor 114/PUU-XX/2022 - Yuniar Riza Hakiki; Zaqil Widad (Fakultas Hukum Universitas Islam Indonesia, 2023)
The Constitutional Court (MK) ruled on case No. 114/PUU-XX/2022 which essentially rejected a request for an open proportional system to be declared unconstitutional. The Court refuted all of the petitioner's arguments along with an explanation of the constitutionality of the open proportional system. Nevertheless, the Constitutional Court realizes conceptually and in practice that whatever electoral system is chosen by the framer of the law still has advantages and disadvantages. So, what is the consideration of the Constitutional Court rejecting the application for the cancellation of the open proportional system? And is an open proportional system an electoral system whose constitutionality is absolute? This paper is written based on legal research with normative juridical methods that use a case approach. The primary legal material used is the Constitutional Court decision No. 114/PUU-XX/2022, and is supported by secondary legal material. This paper concludes, first, that the Constitutional Court rejects the application for cancellation of the open proportional system based on 6 (six) points of rebuttal to the applicant's arguments, 1 (one) argument for the Constitutional Court's stance that improvements and improvements to the implementation of elections can be carried out in various aspects without having to change the system, and based on the original intent and systematic interpretation of Article 22E paragraph (3) and Article 1 paragraph (2) of the 1945 Constitution; second, the open proportional system is not an electoral system whose constitutionality is absolute, because the Constitutional Court emphasized that the electoral system is an option for the framer of the law that remains open to the possibility of being adjusted to the dynamics and needs of holding general elections. However, the Constitutional Court provides a number of constitutional limitations that must be considered by the framers of the law if they are going to make improvements to the current system